Retrospective diagnostic accuracy study of abbott RealTime MTB against Xpert MTB/RIF Ultra and Xpert MTB/RIF for the diagnosis of pulmonary tuberculosis and susceptibility to rifampin and isoniazid treatment - Howlett, Patrick; Nabeta, Pamela; Tukvadze, Nestan; Schumacher, Samuel G.; Denkinger, Claudia M. (Microbiology spectrum, 2021)
In 2019, 10 million people fell ill with tuberculosis (TB), of whom 1.4 million died. - There are few comparative studies of diagnostic assays, particularly those aiming - to be used in high-throughput laboratories.
Gesehen am 18.11.2021